Central nervous system activity of the methanol extracts of Helianthus annuus seeds in mice model - Islam, Rubab Tarannum; Islam, Ahmed Tanjimul; Hossain, Mir Monir; Mazumder, Kishor (International Current Pharmaceutical Journal, 2015)
Helianthus annuus seeds contain various chemical components and evaluate different biological activities. The present study was carried out to investigate the central nervous system (CNS) activity of methanolic extract of Helianthus annuus seeds in mice model. General behaviour, antidepressant activity and anxiolytic activity was observed. The results revealed that the methanol extract of Helianthus annuus seeds at 100 and 200 mg/kg caused a significant increase in the spontaneous activity (general behavioural profile), moderate increase in anxiolytic activity (light-dark box and elevated plus maze test) and remarkable increase in antidepressant activity (tail suspension test). The results suggest that methanol extract of Helianthus annuus exhibit significant antidepressant and moderate anxiolytic activity in tested animal models. Islam et al., International Current Pharmaceutical Journal, December 2015, 5(1): 1-4